An Integrated Intervention for the Treatment of Serious Psychosomatic Illnesses Such As Cancer - Fortuna, Fabiola (International Journal of Innovative Research in Medical Science, 2019)
Background: The term “psychosomatic”often is improperly used: currently psychosomatic means both the set of morbid states that can create mental illness, and the psychic implications in the aetiopathogenesis of organic diseases. Personally, I think it is more useful to focus on the question from this last point of view. I think also that the real psychosomatic disorders should also include cancer, cardiovascular diseases and multiple sclerosis. This does not imply that the etiopathogenesis of these diseases might solely be of a psychic nature, but we should also hypothesize this possibility, along with hypothesizing the contributing factor of psychological causes. Actually the hypothesis most credible is that the serious organic diseases such as cancer, originate from three main factors: genetic, environmental and psychic. Methods: The N.M.P.M.P. (New Psychotherapeutic Method Psychosomatic Diseases) is a integrate method that consists in individual collogues, psychophysical relaxation techniques and group psicotherapy with analytical psychodrama created by Eugenie and Paul Lemoine. Results: Even though it is not possible to get statisical data, the NMPMP’s results are very promising: the method are generated a significant improvement in health conditions for patients; from alleviation of chemotherapy symptoms to complete remission of the symptoms related to neoplasie. Conclusions: The clinical experience described shows to be strategically indispensable an integrate psychological intervention for patients suffering from serious organic diseases.